1987
DOI: 10.1093/ageing/16.3.189
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Restriction of Acitivty in Old People After Falls

Abstract: The levels of activity of two populations of fall victims (at home and in an institution) were studied before and then 6 months after an apparently minor fall, in comparison with a control group. The fall victims had a lower level of activity than the controls. They walked less indoors, and found it more difficult to get out. These differences may be considered predictive factors for falls. It was also found that the falls resulted in a restriction of activity and appear to be a factor that aggravates and acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
100
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(103 citation statements)
references
References 0 publications
2
100
0
Order By: Relevance
“…Besides physical activity many other factors affect the risk of falls, and the relationship between physical activity and falls is not a simple cause and effect relationship. It has been shown that fear of falling in elderly leads to less physical activity (29,30) and nonparticipation in recreational physical activities (31). To approximate a uni-directional relationship between physical activity and falls, subjects who suffered a lower extremity fracture during the last year were excluded from the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Besides physical activity many other factors affect the risk of falls, and the relationship between physical activity and falls is not a simple cause and effect relationship. It has been shown that fear of falling in elderly leads to less physical activity (29,30) and nonparticipation in recreational physical activities (31). To approximate a uni-directional relationship between physical activity and falls, subjects who suffered a lower extremity fracture during the last year were excluded from the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Fear of falling (FOF) is common in older people Vellas et al 4 indicated that fear of falling may lead to a loss of confidence and reduced activity, resulting in a loss of independence. Furthermore, fear of falling may lead to a decreased mobility 5,6 functional decline [5][6][7] falls 8 and institutionalization 6 and consequently to a decrease in quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Falls have the highest percentage of injury-related deaths and fall related injuries have the highest cost after vehicle injuries [4], [5]. The mortality rate of fall increases dramatically with age and 70% of accidental deaths in persons above 75 are caused by falling [6].…”
Section: Introductionmentioning
confidence: 99%